Tugas Dan Kewenangan DKP (Dewan Kehormatan Pusat) Dalam Penegakan Etik Notaris - Fadlan, Billy; Jamilah, Lina (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research examines the role, function, and duties of the Dewan Kehormatan Pusat (DKP) in enforcing notary ethics and imposing sanctions on violators. Notaries, as public officials, are responsible for creating authentic legal documents, which requires adherence to a strict code of ethics to maintain their professionalism and public trust. The study uses a juridical-normative approach to analyze the processes DKP follows in investigating ethical violations, from the initial report to the final decision, and the types of sanctions it imposes, ranging from warnings to the revocation of notary membership. Findings highlight the critical role DKP plays in safeguarding the integrity of the notary profession, ensuring accountability, and promoting continuous professional development through education and guidance. The research concludes by recommending improvements in DKP's operational procedures, reporting systems, and collaboration with other legal bodies to further enhance its effectiveness.